2018
DOI: 10.7759/cureus.2607
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Survival After Treating Cardiac Metastasis With Radiation and Immune Therapy: A Case Report

Abstract: Cardiac metastases are a rare clinical entity and they generally portend a poor prognosis. Management is generally directed toward symptom control and maintaining cardiac function; however, long-term survival is rare. Here, we report a case of isolated metastatic urothelial cell carcinoma to the right ventricle that was functionally limiting the patient. The metastasis was successfully palliated for 17 months following radiation and immune therapy; however, disease progression in and around his heart ultimatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
(12 reference statements)
0
7
0
2
Order By: Relevance
“…[ 19 ] In general, it is known that the prognosis is poor in cases of metastasis from various primary cancers to the heart, and the rate of detection at autopsy was confirmed to be about 7.1%. [ 12 , 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] In general, it is known that the prognosis is poor in cases of metastasis from various primary cancers to the heart, and the rate of detection at autopsy was confirmed to be about 7.1%. [ 12 , 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Бюллетень сибирской медицины. 2020; 19 (4): 241-246 рассмотрения вопроса о паллиативном стентировании ветви, вовлеченной в метастаз, пациент скончался [1]. Приведенный клинический случай поднимает вопрос о рамках инвазивной помощи больным с отдаленными метастазами в сердце, который требует индивидуального подхода, чтобы не подвергать пациентов излишним страданиям.…”
Section: Discussionunclassified
“…Метастазирование уротелиального рака мочевого пузыря (УРМП) в сердце относится к редким и опасным случаям в клинической практике. К настоящему времени обнаружено лишь пять описаний метастазирования в сердце УРМП [1][2][3][4][5], и еще девять случаев в работе N. Ueda и соавт. [6], где приводится таблица опубликованных на тот момент описаний метастазирования урогенитального рака (УР) в сердце, при этом девять из них имели локализацию первичной опухоли в мочевом пузыре (МП).…”
Section: Introductionunclassified
“…Data are lacking on cardiac SBRT in patients with pre-existing cardiac conditions. Arscott et al [13] reported a case of a patient with metastatic urothelial carcinoma to the heart who presented in heart block because of a right ventricular metastasis and developed myocarditis and dyssynchrony requiring placement of a biventricular pacemaker, but this patient did not receive SBRT.…”
Section: Discussionmentioning
confidence: 99%